2013
DOI: 10.1159/000355752
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Suicidal Erythrocyte Death by Increased Extracellular Phosphate Concentrations

Abstract: Background/Aim: Anemia in renal insufficiency results in part from impaired erythrocyte formation due to erythropoietin and iron deficiency. Beyond that, renal insufficiency enhances eryptosis, the suicidal erythrocyte death characterized by phosphatidylserine-exposure at the erythrocyte surface. Eryptosis may be stimulated by increase of cytosolic Ca2+-activity ([Ca2+]i). Several uremic toxins have previously been shown to stimulate eryptosis. Renal insufficiency is further pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
102
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 61 publications
(86 reference statements)
2
102
0
2
Order By: Relevance
“…The concentration of Na + and K + electrolytes in the extracellular fluid is maintained by the transport mechanisms occurring across the cell membranes and by the kidneys [39]. In agreement with the finding of Allison et al [40], Gava et al [5]; Bhadranna and Ahmed [41,42], the present study recorded…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The concentration of Na + and K + electrolytes in the extracellular fluid is maintained by the transport mechanisms occurring across the cell membranes and by the kidneys [39]. In agreement with the finding of Allison et al [40], Gava et al [5]; Bhadranna and Ahmed [41,42], the present study recorded…”
Section: Discussionsupporting
confidence: 91%
“…The concentrations of K+ in urine and serum of Nx rats remained almost constant in comparison to sham control values. Similar studies reported earlier by Schultze et al [44]; Bank and Aynedjian [45] and Bhadranna & Ahmed [41,42]. Housing of Nx rats in the Egyptian pyramids enhance electrolytes levels in urine and serum suggesting its role in homeostasis in the body of Nx rats.…”
Section: Journal Of Complementary Medicine and Alternative Healthcaresupporting
confidence: 86%
“…Naphthazarin sensitizes breast cancer cells to the pro-apoptotic effect of radiation [6]. Naphthazarin is effective by various cellular mechanisms including oxidative stress [7,8] [13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and accelerated eryptosis contributes to the pathophysiology of several clinical conditions, such as iron deficiency, phosphate depletion, malignancy, metabolic syndrome, diabetes, hepatic and renal insufficiency, dehydration, hyperphosphataemia, haemolytic uraemic syndrome, sepsis, malaria, sickle cell disease, thalassaemia and Wilson's disease [13,[34][35][36].The present study explored whether naphthazarin is able to trigger suicidal death of erythrocytes, that is cells devoid of mitochondria and nuclei, key organelles in the execution of apoptosis. To this end, erythrocytes drawn from healthy volunteers were treated with naphthazarin, and phosphatidylserine surface abundance, cell volume, [Ca 2+ ] i , oxidative stress and ceramide abundance were determined.…”
mentioning
confidence: 99%
“…Eryptosis could further be triggered by the activation of casein kinase 1a [13], Janus-activated kinase JAK3 [13], protein kinase C [13] or p38 kinase [13], and by inhibition of AMP-activated kinase AMPK [13], cGMP-dependent protein kinase [13], PAK2 kinase [13] or sorafenib/sunitinib-sensitive kinases [13]. Eryptosis may be elicited by a wide variety of chemicals [13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and accelerated eryptosis contributes to the pathophysiology of several clinical conditions, such as iron deficiency, phosphate depletion, malignancy, metabolic syndrome, diabetes, hepatic and renal insufficiency, dehydration, hyperphosphataemia, haemolytic uraemic syndrome, sepsis, malaria, sickle cell disease, thalassaemia and Wilson's disease [13,[34][35][36].…”
mentioning
confidence: 99%
“…Eryptosis is elicited by a wide variety of xenobiotics [13,, including tannic acid [48], honokiol [62], gossypol [46], gambogic acid [63], tanshinone II A [47], apigenin [64], ursolic acid [65], thymoquinone [66], oridonin [67] and a-lipoic acid [14]. Moreover, eryptosis is accelerated in a wide variety of clinical conditions [11,68], including sepsis [69], fever [16], malaria [29,[70][71][72][73], sickle cell disease [43,[74][75][76][77][78][79][80], Wilson's disease [81], iron deficiency [82], malignancy [83], metabolic syndrome [44], diabetes [30], renal insufficiency [39,84,85], haemolytic uremic syndrome [86], hyperphosphataemia [87] and phosphate depletion [68].…”
mentioning
confidence: 99%